Psychological characteristics of emotional intelligence of teachers working with children of developmental disorders - Sayko, Khristina (Journal of Education Culture and Society, 2020)
The paper discusses emotional intelligence as a factor of effective teaching. Emotional intelligence, in broad interpretation, is defined as the ability to differentiate between posi-tive and negative emotions, and the ability to change one’s emotional condition from a poor to a better one. Internal and external components are inherent in the emotional com-ponent, and they can provide stress protecting and adaptive functions of this integral con-cept. Also it highlights psychological characteristics of teachers working with children with developmental disorders. Psychological requirements for specialists who work with indi-viduals with special educational needs include psychological willingness of a personality for this work. This willingness can be considered as an integrated quality of a personality including a system of motivation, knowledge, skills, certain experience, personal qualities that ensure successful activity.